The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12879-021-06545-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction rules for the diagnosis of neuritis in leprosy

Abstract: Background Diagnosing neuritis in leprosy patients with neuropathic pain or chronic neuropathy remains challenging since no specific laboratory or neurophysiological marker is available. Methods In a cross-sectional study developed at a leprosy outpatient clinic in Rio de Janeiro, RJ, Brazil, 54 individuals complaining of neural pain (single or multiple sites) were classified into two groups (“neuropathic pain” or “neuritis”) by a neurological sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…10,[24][25][26][27] Recent studies suggest an annual prevalence of 15% of NP in leprosy patients, and it is known that this symptom has a great impact on patients' quality of life. 28 Although historically chronic pain syndromes are more prevalent among women, leprosy and NP are more frequent among men, 29 which is in agreement with what was found in our cohort, in which 55.6% of patients were male. Furthermore, the age group that reflects the economically active population is the most affected in many global studies on leprosy and NP, as confirmed in our study, in which the mean age of patients was 55 years.…”
Section: Discussionsupporting
confidence: 90%
“…10,[24][25][26][27] Recent studies suggest an annual prevalence of 15% of NP in leprosy patients, and it is known that this symptom has a great impact on patients' quality of life. 28 Although historically chronic pain syndromes are more prevalent among women, leprosy and NP are more frequent among men, 29 which is in agreement with what was found in our cohort, in which 55.6% of patients were male. Furthermore, the age group that reflects the economically active population is the most affected in many global studies on leprosy and NP, as confirmed in our study, in which the mean age of patients was 55 years.…”
Section: Discussionsupporting
confidence: 90%
“…The term neuritis has been used in numerous ways in the leprosy literature, sometimes describing the acute episode, as in a leprosy reaction, and sometimes as the silent nerve impairment caused by the disease (13). Limitations are present in this study, including the fact that the data is retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients with leprosy reactions were treated with corticosteroids. Neuropathic pain was always evaluated by a neurologist, and its diagnosis was based on the presence of pain in a neuro-anatomically plausible area with confirmed negative or positive sensory signs (13).…”
Section: Patients and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil positif menunjukkan bahwa pasien memiliki MB. Namun, hasil negatif tidak mengesampingkan diagnosis klinis kusta dan tidak serta merta mengklasifikasikan pasien sebagai penderita PB (3,6,7).…”
Section: Diagnosisunclassified